2013
DOI: 10.1124/jpet.112.201426
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Low-Dose Administration of the Monoacylglycerol Lipase Inhibitor JZL184 Retains Cannabinoid Receptor Type 1–Mediated Antinociceptive and Gastroprotective Effects

Abstract: The monoacylglycerol lipase (MAGL) inhibitor 4-nitrophenyl 4-(dibenzo [d] [1,3]dioxol-5-yl(hydroxy)methyl)piperidine-1-carboxylate (JZL184) produces antinociceptive and anti-inflammatory effects. However, repeated administration of high-dose JZL184 (40 mg/kg) causes dependence, antinociceptive tolerance, crosstolerance to the pharmacological effects of cannabinoid receptor agonists, and cannabinoid receptor type 1 (CB 1 ) downregulation and desensitization. This functional CB 1 receptor tolerance poses a hurdl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
148
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(174 citation statements)
references
References 39 publications
(59 reference statements)
16
148
4
Order By: Relevance
“…The anxiogenic and depression-like effects observed in the control mice cannot be related to the dosage of JZL184, as the dose used here (8 mg/kg/day) did not induce cannabimimetic effects, in agreement with previous works (Long et al, 2009a;Schlosburg et al, 2010;Wise et al, 2012). The moderate dose employed here should also be devoid of the decreased CB1 receptor function observed at high doses of the drug (Schlosburg et al, 2010;Kinsey et al, 2013), although, differently from these previous reports, in our case the duration of the treatment was longer. As JZL184-induced increase in 2-AG levels is dependent on the dose as well as the duration of the treatment (Kinsey et al, 2013), one possibility is that in healthy mice (controls) chronic administration of JZL184 may have exacerbated the 2-AG-signaling, along with an eventual loss of MAGL activity-dependent neuroprotective mechanisms (Nomura et al, 2011), to an extent sufficient to produce the behavioral responses observed, and which usually occur at high doses of CB1 receptor agonists (Rey et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The anxiogenic and depression-like effects observed in the control mice cannot be related to the dosage of JZL184, as the dose used here (8 mg/kg/day) did not induce cannabimimetic effects, in agreement with previous works (Long et al, 2009a;Schlosburg et al, 2010;Wise et al, 2012). The moderate dose employed here should also be devoid of the decreased CB1 receptor function observed at high doses of the drug (Schlosburg et al, 2010;Kinsey et al, 2013), although, differently from these previous reports, in our case the duration of the treatment was longer. As JZL184-induced increase in 2-AG levels is dependent on the dose as well as the duration of the treatment (Kinsey et al, 2013), one possibility is that in healthy mice (controls) chronic administration of JZL184 may have exacerbated the 2-AG-signaling, along with an eventual loss of MAGL activity-dependent neuroprotective mechanisms (Nomura et al, 2011), to an extent sufficient to produce the behavioral responses observed, and which usually occur at high doses of CB1 receptor agonists (Rey et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…The moderate dose employed here should also be devoid of the decreased CB1 receptor function observed at high doses of the drug (Schlosburg et al, 2010;Kinsey et al, 2013), although, differently from these previous reports, in our case the duration of the treatment was longer. As JZL184-induced increase in 2-AG levels is dependent on the dose as well as the duration of the treatment (Kinsey et al, 2013), one possibility is that in healthy mice (controls) chronic administration of JZL184 may have exacerbated the 2-AG-signaling, along with an eventual loss of MAGL activity-dependent neuroprotective mechanisms (Nomura et al, 2011), to an extent sufficient to produce the behavioral responses observed, and which usually occur at high doses of CB1 receptor agonists (Rey et al, 2012). Indeed, JZL184 and combo treatments induced a statistically significant higher increase in 2-AG level in controls as compared with CUS animals ( Figure 5).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…These adverse effects following high-dose 151 treatment might be attributed to its off-target inhibition of FAAH, consistent with the previous finding that dual FAAH/MAGL inhibition produced cannabimimetic side effects. 159,160 Furthermore, the administration of 151 was demonstrated to produce gastroprotective and antidepressant-like effects post a 4 mg/kg intraperitoneal injection. 160,161 The determination of the binding mechanism indicated that 151 covalently and irreversibly bound to MAGL through the formation of the carbamylated-enzyme adduct ( Figure 56).…”
Section: Carbamatesmentioning
confidence: 99%
“…Against this background, here I would like to make a warning that selective inhibitors like JZL184 (especially if used at quite high concentrations) might hit unexpected offtargets that significantly contribute to the biological activity of eCBs. Incidentally, besides potentially unknown off-targets JZL184 inhibits FAAH with an IC 50 of 4 mM, and can affect CB 1 -dependent signaling through down-regulation and desensitization of this receptor [11]. Another major point that I would like to make is that eCBs have been clearly demonstrated to be good substrates for the key-enzymes responsible for the classical arachidonate cascade (i.e., cyclooxygenases and lipoxygenases), leading to the generation of oxygenated derivatives endowed with distinct biological activities [12].…”
mentioning
confidence: 99%